Digital Twin Technology: Revolutionizing Modern Healthcare Systems - Jaswanth Kumar Vuggumudi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Digital Twin technology represents a transformative advancement in healthcare delivery and management, enabling the creation of virtual replicas for patients, medical devices, and healthcare processes. This innovative technology integrates real-time data acquisition, historical analysis, and advanced machine learning algorithms to create dynamic simulations of physical healthcare entities. The implementation encompasses multiple architectural layers, from data integration to application interfaces, facilitating comprehensive patient monitoring, predictive diagnostics, and personalized treatment optimization. Through sophisticated security protocols and scalable infrastructure, healthcare digital twins enhance operational efficiency, improve patient outcomes, and revolutionize medical device management. The technology demonstrates significant capabilities in early disease detection, treatment planning, and resource optimization while maintaining strict compliance with healthcare standards. The integration with emerging technologies like AI and IoT further amplifies its impact, enabling proactive interventions, reducing readmission rates, and streamlining clinical workflows across healthcare institutions.